2020
DOI: 10.3390/ijerph17144948
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Preventive Dental Treatment of Adolescents in Korea

Abstract: We conducted a multilevel analysis to identify factors affecting adolescents’ preventive dental treatment experience in South Korea. We sampled 72,435 students who participated in the 9th Korea Youth Risk Behavior Web-based Survey. The individual-level variables were divided into demographic factors, socioeconomic factors, oral health behavioral factors, and oral symptom experience factors. The regional-level variables included oral health resources, rate of students receiving oral health education at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
1
0
0
Order By: Relevance
“…The study markedly found that the SDS teams had a substantially lower travel burden for primary and secondary schoolchildren in urban areas, indicating better accessibility to primary oral health services than their rural counterparts. Study findings also supported the idea that the SDS programme could be expanded to private schools in urban districts as these areas offer more oral healthcare facilities and the mobile dental team has a lower travel burden [33][34][35]. However, more detailed data is required to support the readiness of the SDS programme to expand to private schools.…”
Section: Discussionsupporting
confidence: 62%
“…The study markedly found that the SDS teams had a substantially lower travel burden for primary and secondary schoolchildren in urban areas, indicating better accessibility to primary oral health services than their rural counterparts. Study findings also supported the idea that the SDS programme could be expanded to private schools in urban districts as these areas offer more oral healthcare facilities and the mobile dental team has a lower travel burden [33][34][35]. However, more detailed data is required to support the readiness of the SDS programme to expand to private schools.…”
Section: Discussionsupporting
confidence: 62%